Efeito do cálcio na dieta sobre o crescimento e a sobrevivência de juvenis de jundiá Rhamdia quelen (Heptapteridae) em diferentes pH da água - Copatti, Carlos Eduardo (2005)
The purpose of this study was to verify the effect of dietary Ca2+ on growth and survival of silver catfish fingerlings (Rhamdia quelen) exposed to different water pH (5.5; 7.5 and 9.0). Silver catfish fingerlings were randomly placed in a termo-regulated water re-use system with twelve 250 L tanks, two 1000 L biofilters and a 2000 L reservoir with medium flow of 3.84 L min-1 tank. Stocking density was 0.16 fingerlings L-1. To prepare the treatment diets, the control diet (0.08% Ca2+) was supplemented with CaCO3 to yield experimental diets with 0.64; 0.95 and 2.39% Ca2+. There were three replicates/treatment. Survival was higher than 93.9% in all treatments. Exposure of silver catfish fingerlings to alkaline or acid water reduced growth, and this effect was not ameliorated by dietary Ca2+ supplementation. Moreover, best dietary Ca2+ range for silver catfish fingerling growth is 0.08-0.64%, mainly when fingerlings were maintained in water with neutral pH.